Battery type capacitor and preparation method thereof

By using an integrated porous graphite film as the positive electrode sheet and lithium titanate/carbon composite material as the active substance of the negative electrode sheet in the battery type capacitor, the problem of low energy density and power density in the prior art is solved, and higher battery performance is achieved.

CN119626787APending Publication Date: 2025-03-14QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721430.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing electric double layer supercapacitors have low energy density and power density, which cannot meet the actual use needs.

Method used

An integrated porous graphite film is used as the positive electrode sheet, and the active substance in the negative electrode sheet is lithium titanate/carbon composite material. Anion embedded in the porous graphite film and lithium ions embedded in the lithium titanate/carbon composite material are improved to improve the working voltage range and battery performance.

Benefits of technology

The energy density and power density of battery-type capacitors have been significantly improved, the working voltage range has been expanded to 1.5~5.0V, and the charge and discharge cycle performance has also been optimized.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a battery type capacitor which comprises a shell, a positive plate, a negative plate, a diaphragm and electrolyte, the positive plate is an integrated porous graphite film, the diameter of holes is 10-100 microns, the porosity is 15-40%, the surface density is 7-12mg / cm < 2 >, and the electronic conductivity is 50-200S / cm; the negative plate is composed of a negative current collector and negative slurry coated on the negative current collector, the negative slurry is composed of a negative active material, a conductive agent and a binder, and the negative active material is a lithium titanate / carbon composite material. The invention also discloses a preparation method of the battery type capacitor. The battery type capacitor disclosed by the invention has the advantages of high energy density, high power density and long charge-discharge service life, and the preparation method is simple and easy for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemical energy storage, and in particular relates to a battery-type capacitor and a preparation method thereof. Background Art

[0002] As the world attaches great importance to climate change and energy conservation and carbon reduction, the new energy industry has become one of the strategic emerging industries in the new century. As an important support and auxiliary technology for the new energy industry, the new energy storage material industry has attracted much attention from all parties. In my country, with the rapid development of pure electric vehicles and hybrid vehicles, the steady advancement of smart grids, the large-scale access of renewable energy such as wind and solar energy to the grid, and the growth of regional peak loads, various application problems have also emerged, which have put forward higher requirements on the energy density, power density and service life of electrochemical energy storage devices.

[0003] Supercapacitors have the characteristics of high power density and long cycle life. A typical example is a double-layer supercapacitor, whose positive and negative active materials are porous carbon. When charging, the high specific surface area of ​​porous carbon is used to physically adsorb charges for energy storage. Its operating voltage range is 0-2.7V, power density ≥5kW / kg, and charge and discharge cycle life is 100,000 times. However, its porous carbon electrode has low electronic conductivity (0.7-0.85S / cm), low energy density (~5Wh / kg), and cannot meet the needs of actual use. Therefore, it is of great significance to develop battery-type capacitors with higher energy density and high power density. Summary of the invention

[0004] In order to solve the above problems, the present invention aims to provide a battery-type capacitor and a method for preparing the same.

[0005] To achieve the above purpose, the present invention adopts the following technical solution:

[0006] A battery-type capacitor comprises a shell, a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte, wherein the positive electrode sheet is an integrated porous graphite film; the negative electrode sheet is composed of a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, wherein the negative electrode slurry is composed of a negative electrode active material, a conductive agent, and a binder, and the negative electrode active material is a lithium titanate / carbon composite material.

[0007] The diameter of the pores in the integrated porous graphite membrane is 10 to 100 microns, the porosity is 15% to 40%, and the surface density is 7 to 12 mg / cm 2 , the electronic conductivity is 50~200S / cm.

[0008] The integrated porous graphite film is one of a porous polyimide graphite film, a porous expanded graphite film, and a porous graphene film.

[0009] The weight ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode slurry is 90-95:2.5-5:2.5-5;

[0010] The conductive agent is one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and graphitized carbon fibers;

[0011] The binder is one or more of polyvinylidene fluoride, acrylonitrile multipolymer, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and styrene-butadiene rubber.

[0012] The surface density of the negative electrode slurry coated on the negative electrode current collector is 15-26 mg / cm 2 .

[0013] The material of the diaphragm is one of polypropylene, polyethylene and cellulose, and the porosity of the diaphragm is 62% to 75%.

[0014] A preparation method for a battery-type capacitor comprises alternately stacking the negative electrode sheets and the positive electrode sheets, providing a diaphragm between two adjacent sheets, assembling a winding core, and placing the negative electrode sheets on both sides of the winding core; then vacuum drying the assembled winding core and placing it in a shell, injecting an electrolyte into the shell, and sealing the shell.

[0015] The positive electrode sheet is made by cutting an integrated porous graphite film and baking it in vacuum.

[0016] The negative electrode sheet is prepared by mixing the negative electrode active material with the conductive agent, the binder and the solvent according to the weight ratio to form a negative electrode slurry, and then coating the slurry on the negative electrode collector to form a surface density of 15 to 26 mg / cm 2 The film is then dried, rolled, cut into pieces, and vacuum-baked to make the negative electrode sheet.

[0017] The advantages and positive effects of the present invention are:

[0018] The present invention uses an integrated porous graphite film as the positive electrode sheet, and the active material in the negative electrode sheet is a lithium titanate / carbon composite material. During charging and discharging, the anions in the electrolyte are embedded in the integrated porous graphite film as the positive electrode sheet, and the lithium ions are embedded in the lithium titanate / carbon composite material. The operating voltage range is 1.5 to 5.0V, which is much higher than the existing double-layer capacitors, and the energy density is improved. The use of an integrated porous graphite film with high electronic conductivity can improve the power density of the battery-type capacitor. The anions can ensure the stability of the electrode structure during the embedding process and improve the charge and discharge cycle performance of the battery-type capacitor. The negative electrode uses a lithium titanate / carbon composite material as the active material in the negative electrode sheet so that the potential for inserting / extracting lithium ions is maintained at 1.55V vs. Li + / Li, even when charged and discharged at a large current, the charge and discharge cycle performance is excellent. DETAILED DESCRIPTION

[0019] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0020] Example 1

[0021] (1) Positive electrode production: pore size 50 μm, porosity 30%, surface density 10 mg / cm 2 The porous polyimide graphite film was measured to have an electronic conductivity of 200S / cm. It was cut into pieces with a size of 20.1cm×15.1cm and vacuum-baked to make a positive electrode sheet.

[0022] (2) Negative electrode sheet preparation: The negative electrode active material lithium titanate / carbon, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride were mixed in a weight ratio of 94:3.5:2.5, and the solvent N-methyl-2-pyrrolidone was added to prepare the negative electrode slurry, which was then coated on the negative electrode current collector. The surface density of the negative electrode slurry coated on the current collector was 21 mg / cm 2 After drying, rolling and cutting, the size is 19.7cm×14.7cm, and after vacuum baking, it is made into a negative electrode sheet.

[0023] (3) Assembly: A cellulose separator with a porosity of 70% is selected as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, and the outermost two sides of the winding core are always kept as negative electrode sheets.

[0024] (4) Liquid injection and sealing: After the core is vacuum dried, it is placed in a shell, and an electrolyte of 1.0 mol / L lithium hexafluorophosphate / ethyl methyl carbonate-cyclopentane sulfone (the volume ratio of solvent ethyl methyl carbonate and cyclopentane sulfone is 1:4) is injected into the shell and sealed.

[0025] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.3Ah, the mass energy density is 115.1Wh / kg, the volume energy density is 194.1Wh / L, the power density at 10C rate current is 5.95kW / kg, the 10C discharge capacity / 1C discharge capacity is 94.5%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 87.8%.

[0026] Example 2

[0027] (1) Positive electrode production: pore size 50 μm, porosity 30%, surface density 10 mg / cm 2The porous expanded graphite film was measured to have an electronic conductivity of 85 S / cm. It was cut into pieces with a size of 20.1 cm × 15.1 cm and vacuum-baked to make positive electrode sheets.

[0028] (2) Negative electrode sheet preparation: The negative electrode active material lithium titanate / carbon, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride were mixed in a weight ratio of 94:3.5:2.5, and the solvent N-methyl-2-pyrrolidone was added to prepare the negative electrode slurry, which was then coated on the negative electrode current collector. The surface density of the negative electrode slurry coated on the current collector was 21 mg / cm 2 After drying, rolling and cutting, the size is 19.7cm×14.7cm, and after vacuum baking, it is made into a negative electrode sheet.

[0029] (3) Assembly: A cellulose separator with a porosity of 70% is selected as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, and the outermost two sides of the winding core are always kept as negative electrode sheets.

[0030] (4) Liquid injection and sealing: After the core is vacuum dried, it is placed in a shell, and an electrolyte of 1.0 mol / L lithium hexafluorophosphate / ethyl methyl carbonate-cyclopentane sulfone (the volume ratio of solvent ethyl methyl carbonate and cyclopentane sulfone is 1:4) is injected into the shell and sealed.

[0031] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.2Ah, the mass energy density is 114.3Wh / kg, the volume energy density is 190.2Wh / L, the power density at 10C rate current is 5.78kW / kg, the 10C discharge capacity / 1C discharge capacity is 92.3%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 84.9%.

[0032] Example 3

[0033] (1) Positive electrode production: pore size 50 μm, porosity 30%, surface density 10 mg / cm 2 The porous graphene film was measured to have an electronic conductivity of 145 S / cm. It was cut into pieces with a size of 20.1 cm × 15.1 cm and vacuum-baked to make a positive electrode sheet.

[0034] (2) Negative electrode sheet preparation: The negative electrode active material lithium titanate / carbon, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride were mixed in a weight ratio of 94:3.5:2.5, and the solvent N-methyl-2-pyrrolidone was added to prepare the negative electrode slurry, which was then coated on the negative electrode current collector. The surface density of the negative electrode slurry coated on the current collector was 21 mg / cm 2After drying, rolling and cutting, the size is 19.7cm×14.7cm, and after vacuum baking, it is made into a negative electrode sheet.

[0035] (3) Assembly: A cellulose separator with a porosity of 70% is selected as the separator, and the sheets are stacked in the order of negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet / / separator / / positive electrode sheet / / separator / / negative electrode sheet… to form a winding core, and the outermost two sides of the winding core are always kept as negative electrode sheets.

[0036] (4) Liquid injection and sealing: After the core is vacuum dried, it is placed in the shell, and the electrolyte is injected into the shell to seal it.

[0037] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.2Ah, the mass energy density is 114.8Wh / kg, the volume energy density is 193.5Wh / L, the power density at 10C rate current is 5.85kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.3%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 85.9%.

[0038] Example 4

[0039] The pore size of the porous polyimide graphite membrane in Example 1 was changed to 10 μm. At this time, the surface density of the porous polyimide graphite membrane was 10.2 mg / cm 2 , the rest is the same as Example 1.

[0040] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.7Ah, the mass energy density is 114.2Wh / kg, the volume energy density is 193.9Wh / L, the power density at 10C rate current is 5.32kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.5%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 85.4%.

[0041] Example 5

[0042] The pore size of the porous polyimide graphite membrane in Example 1 was changed to 100 μm. At this time, the surface density of the porous polyimide graphite membrane was 9.8 mg / cm 2 , the rest is the same as Example 1.

[0043] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 19.5Ah, the mass energy density is 114.8Wh / kg, the volume energy density is 189.3Wh / L, the power density at 10C rate current is 6.03kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.2%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 88.6%.

[0044] Example 6

[0045] The porosity of the porous polyimide graphite film in Example 1 was changed to 40%. At this time, the surface density of the porous polyimide graphite film was 9.7 mg / cm 2 , the rest is the same as Example 1.

[0046] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 19.1Ah, the mass energy density is 112.1Wh / kg, the volume energy density is 188.5Wh / L, the power density at 10C rate current is 6.05kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.2%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 88.7%.

[0047] Example 7

[0048] The porosity of the porous polyimide graphite film in Example 1 was changed to 15%. At this time, the surface density of the porous polyimide graphite film was 10.1 mg / cm 2 , the rest is the same as Example 1.

[0049] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.6Ah, the mass energy density is 114.3Wh / kg, the volume energy density is 193.8Wh / L, the power density at 10C rate current is 5.35kW / kg, the 10C discharge capacity / 1C discharge capacity is 93.6%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 85.6%.

[0050] Example 8

[0051] The surface density of the porous polyimide graphite film in Example 1 was changed to 7 mg / cm 2 The surface density of the negative electrode slurry coated on the current collector is 15.1 mg / cm 2 , the rest is the same as Example 1.

[0052] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 19.5Ah, the mass energy density is 113.8Wh / kg, the volume energy density is 193.8Wh / L, the power density at 10C rate current is 6.05kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.3%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 87.9%.

[0053] Example 9

[0054] The surface density of the porous polyimide graphite film in Example 1 was changed to 12 mg / cm 2 The surface density of the negative electrode slurry coated on the current collector is 25.8 mg / cm 2 , the rest is the same as Example 1.

[0055] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 21.8Ah, the mass energy density is 115.9Wh / kg, the volume energy density is 193.3Wh / L, the power density at 10C rate current is 5.28kW / kg, the 10C discharge capacity / 1C discharge capacity is 92.6%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 87.5%.

[0056] Comparative Example 1

[0057] The diameter of the holes in the porous polyimide graphite film in Example 1 is changed to 0 μm, that is, a non-perforated polyimide graphite film is used, and the rest is the same as Example 1.

[0058] Test results: It has been determined that since polyimide graphite film is a highly oriented graphite film, normal anion embedding cannot be achieved when no holes are punched, causing the battery-type capacitor to be unable to charge and discharge normally.

[0059] Comparative Example 2

[0060] The preparation of the positive electrode sheet in Example 1 was changed to: artificial graphite with a particle size of 10 μm, a conductive agent, and a binder were stirred and mixed in a weight ratio of 96:1.5:2.5, and deionized water was added as a solvent to prepare a negative electrode slurry, which was then coated on the positive electrode current collector. The surface density of the positive electrode slurry on the current collector was 10.2 mg / cm 2 After drying, rolling and cutting into pieces with a size of 20.1 cm×15.1 cm, vacuum baking is performed to make a negative electrode sheet. The rest is the same as in Example 1.

[0061] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.1Ah, the mass energy density is 105.3Wh / kg, the volume energy density is 178.4Wh / L, the power density at 10C rate current is 4.47kW / kg, the 10C discharge capacity / 1C discharge capacity is 87.9%, and the capacity retention rate after 5000 10C charge and discharge cycles is 75.7%.

[0062] Comparative Example 3

[0063] The diameter of the pores of the porous polyimide graphite film in Example 1 is changed to 200 μm. At this time, the surface density of the porous polyimide graphite film is 8 mg / cm 2 , the rest is the same as Example 1.

[0064] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 15.2Ah, the mass energy density is 95.9Wh / kg, the volume energy density is 158.1Wh / L, the power density at 10C rate current is 6.08kW / kg, the 10C discharge capacity / 1C discharge capacity is 95.8%, and the capacity retention rate after 10,000 10C charge and discharge cycles is 87.9%.

[0065] Comparative Example 4

[0066] The preparation of the positive and negative electrodes in Example 1 was changed to: artificial graphite with a particle size of 10 μm, a conductive agent, and a binder were stirred and mixed in a weight ratio of 96:1.5:2.5, and deionized water was added as a solvent to prepare positive and negative electrode slurries, which were then coated on the current collector. The surface density of the positive electrode slurry on the current collector was 10 mg / cm 2 The surface density of the negative electrode slurry on the current collector is 20.6 mg / cm 2 After drying, rolling, cutting and vacuum baking, the positive electrode sheet has a size of 20.1 cm×15.1 cm and the negative electrode sheet has a size of 19.7 cm×14.7 cm. The rest is the same as in Example 1.

[0067] Test results: It has been determined that the working voltage of the battery-type capacitor is 1.5-5.0V, the 1C discharge capacity is 20.2Ah, the mass energy density is 90.8Wh / kg, the volume energy density is 172.1Wh / L, the power density at 10C rate current is 5.15kW / kg, the 10C discharge capacity / 1C discharge capacity is 87.4%, and the capacity retention rate after 5000 10C charge and discharge cycles is 74.7%.

[0068] The above-mentioned embodiments only represent several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.

Claims

1. A battery-type capacitor, comprising a housing, a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte, characterized in that: The positive electrode sheet is an integrated porous graphite film; the negative electrode sheet is composed of a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, wherein the negative electrode slurry is composed of a negative electrode active material, a conductive agent, and a binder, and the negative electrode active material is a lithium titanate / carbon composite material.

2. The battery type capacitor according to claim 1, characterized in that: The diameter of the pores in the integrated porous graphite membrane is 10 to 100 microns, the porosity is 15% to 40%, and the surface density is 7 to 12 mg / cm 2 , the electronic conductivity is 50~200S / cm.

3. The battery type capacitor according to claim 2, characterized in that: The integrated porous graphite film is one of a porous polyimide graphite film, a porous expanded graphite film, and a porous graphene film.

4. The battery type capacitor according to claim 1, characterized in that: The weight ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode slurry is 90-95:2.5-5:2.5-5; The conductive agent is one or more of conductive carbon black, conductive graphite, graphene, carbon nanotubes, and graphitized carbon fibers; The binder is one or more of polyvinylidene fluoride, acrylonitrile multipolymer, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and styrene-butadiene rubber.

5. The battery type capacitor according to claim 1 or 4, characterized in that: The surface density of the negative electrode slurry coated on the negative electrode current collector is 15-26 mg / cm 2 .

6. The battery type capacitor according to claim 1, characterized in that: The material of the diaphragm is one of polypropylene, polyethylene and cellulose, and the porosity of the diaphragm is 62% to 75%.

7. A method for preparing a battery-type capacitor according to claim 1, characterized in that: The negative electrode sheets and the positive electrode sheets as described in claim 1 are alternately stacked, a separator is provided between two adjacent sheets, and a winding core is assembled, with the negative electrode sheets being provided on both sides of the winding core; the assembled winding core is then vacuum dried and placed in a shell, and an electrolyte is injected into the shell, and the shell is sealed.

8. The method for preparing a battery-type capacitor according to claim 1, characterized in that: The positive electrode sheet is made by cutting an integrated porous graphite film and baking it in vacuum. The negative electrode sheet is prepared by mixing the negative electrode active material with the conductive agent, the binder and the solvent according to the weight ratio to form a negative electrode slurry, and then coating the slurry on the negative electrode collector to form a surface density of 15 to 26 mg / cm 2 The film is then dried, rolled, cut into pieces, and vacuum-baked to make the negative electrode sheet.